Differences in bacterial diversity, composition, and community networks in lake water across three distinct regions on the Qinghai-Tibet Plateau - Wang, Dandan; Huang, Yuefei; Zhang, Shuo; Liu, Shufeng; Wang, Ting; Yang, Haijiao (Frontiers in Environmental Science, 2022)
We analyze bacterial composition, diversity, geographical distribution, and their community networks in lake water in three adjacent regions on the Qinghai-Tibet Plateau (QTP). Results show that bacterial alpha-diversity indices are much lower in the Hoh Xil (HX) than that in the Yellow River Headwater (YRH) regions and the Qaidam (QD) region. The dominant phyla in QD and YRH are Proteobacteria which account for 42.45 % and 43.64 % of all detected phyla, while Bacteroidetes is the dominant bacterial taxa in HX (46.07 %). Redundancy analysis results suggest that the most important factors in driving bacterial community composition in the three regions are altitude (QD), total nitrogen (YRH), and pH (HX), respectively. Both environmental factors and spatial factors significantly affect the bacterial community composition in QD and HX, while only environmental factors are the major drivers in YRH. Finally, network analyses reveal that the bacterial network structure in QD is more complex than those in YRH and HX, whereas the bacterial network in HX is the most stable, followed by those in QD and YRH